Pemberdayaan Komunitas dengan Optimalisasi Game Mobile Legends Bang Bang melalui Pembelian Skin atau Virtual Item - Istiyani, Istiyani; Purwanto, Eko; Hendrati, Ignatia Martha (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
This study aims to analyze the influence of consumer behavior, namely game satisfaction, consumption value, character identification, and hedonic motivation on the repurchase intention of virtual items in the Mobile Legends Bang Bang game. This study uses a causal associative research method that shows a causal relationship between several variables with this type of quantitative research. Identify 105 respondents of Bang-Bang Mobile Legends game players who have purchased skins or virtual items with the age of 15-40 years spread throughout Indonesia. The data analysis technique uses the Likert scale and uses Partial Least Square to see the influence between variables. The results showed that game satisfaction, consumption value, character identification, and hedonic motivation had a positive and significant effect on the repurchase intention of virtual items in the Bang Bang Mobile Legends game with a significance level below alpha 10 percent. About 80 percent of simultaneous tests of independent variables were able to explain their effect on the repurchase intention of virtual items. This shows that behavior based on the above aspects can affect players' considerations and decisions to purchase skins or virtual items released by the Bang Bang Mobile Legends game, so that the virtual item business can become a lucrative opportunity and market share for game developers and players.